Perkembangan Permukiman di Kecamatan Amurang Timur - Marbun, Mei Randa Ronatio; Lobja, Xaverius Erick; Kumaat, Joyce Christian; Rewah, Fonny (Jurnal Social Science, 2024)
This study aims to identify the development of settlements in the Amurang Timur District. The method used is quantitative research—data collection techniques in the form of observation, documentation, and remote sensing. Researchers use GIS analysis techniques on Landsat 7 and Landsat 8 images. The results of the study show that the development of settlements in Amurang Timur District is influenced by population growth from 2015-2022, there was an increase in settlements of 92.49 hectares. The exponential population growth rate in 2015-2022 was 1.55%.